(3hUjI jMJGL EdjgG cd eQjOs
(3ChdgG (B:s
(3hUjI jMJGL EdjgG cd eQjO WGdH ddeRjO ef GdZfi GdMejO hJCedhg JLOhG GdTaGA s
(3BNQgG (B:s
(3agPG cd eG CQOfG fPcQg dce hQHfG YR hLd hdi GdJhajb dfG hdce Edi eG jMHg hjQVGg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdESchQjGd s
Keywords: (3GdJUha hGdBOGH GdTQYjIs